Picocyanobacteria Community and Cyanophage Infection Responses to Nutrient Enrichment in a Mesocosms Experiment in Oligotrophic Waters - Coello-Camba, Alexandra; Diaz-Rua, Ruben; Duarte, Carlos M.; Irigoien, Xabier; Pearman, John K.; Alam, Intikhab S.; Agusti, Susana (Frontiers in Microbiology, 2020)
Prochlorococcus and Synechococcus are pico-sized cyanobacteria that play a fundamental role in oceanic primary production, being particularly important in warm, nutrient-poor waters. Their potential response to nutrient enrichment is expected to be contrasting and to differ from larger phytoplankton species. Here, we used a metagenomic approach to characterize the responses to nutrient enrichment in the community of picocyanobacteria and to analyse the cyanophage response during a mesocosms experiment in the oligotrophic Red Sea. Natural picoplankton community was dominated by Synechococcus clade II, with marginal presence of Prochlorococcus (0.3% bacterial reads). Increased nutrient input triggered a fast Synechococcus bloom, with clade II being the dominant, with no response of Prochlorococcus growth. The largest bloom developed in the mesocosms receiving a single initial input of nutrients, instead of daily additions. Cyanophage abundances increased during the experiment from 12.6% of total virus reads up to 40% in the treatment with the largest Synechococcus bloom. The subsequent collapse of the bloom pointed to a cyanophage infection on Synechococcus that reduced its competitive capacity, and was then followed by a diatom bloom. The cyanophage attack affected preferentially the most abundant Synechococcus clade II, allowing the proliferation of less abundant clades, and therefore increasing the evenness within the host population. Our results highlight the relevance of host-phage interactions on determining population dynamics and diversity of Synechococcus populations.